An Essential Factor for High Mg2+ Tolerance of Staphylococcus aureus - Armitano, Joshua; Redder, Peter; Guimarães, Vanessa A.; Linder, Patrick (Frontiers in Microbiology, 2016)
Internal bacterial concentration of Mg2+, the most abundant divalent cation in living cells, is estimated to be in the single millimolar range. However, many bacteria will thrive in media with only micromolars of Mg2+, by using a range of intensely studied and highly efficient import mechanisms, as well as in media with very high magnesium concentration, presumably mediated by currently unknown export mechanisms. Staphylococcus aureus has a particularly high Mg2+ tolerance for a pathogen, growing unimpaired in up to 770 mM Mg2+, and we here identify SA0657, a key factor in this tolerance. The predicted domain structure of SA0657 is shared with a large number of proteins in bacteria, archaea and even eukarya, for example CorB from Salmonella and the human CNNM protein family. One of the shared domains, a CBS pair potentially involved in Mg2+ sensing, contains the conserved Glycine326 which we establish to be a key residue for SA0657 function. In light of our findings, we propose the name MpfA, Magnesium Protection Factor A, for SA0657.